Photo-Triggered Synthesis of Sulfonamides in a Sustainable Solvent via Electron Donor-Acceptor Complex - Kamal A.; Singh H.K.; Maury S.K.; Kushwaha A.K.; Srivastava V.; Singh S. (My University, 2025)
A visible-light-triggered synthesis of sulfonamide was developed via an electron donor-acceptor (EDA) complex in the more environmentally friendly green solvent 2-methyltetrahydrofuran (MeTHF). This method offers a novel strategy for synthesizing sulfonamide in high yields at room temperature, without the need of a base, any additional photocatalyst, or transition metals. Simple operation, mild reaction conditions, excellent atom economy, and excellent functional group compatibility are the main advantages of this reaction. © 2023 Wiley-VCH GmbH.